Clinicopathological analysis of clinically occult extrapulmonary lymphangioleiomyomatosis in intra‐pelvic and para‐aortic lymph nodes associated with pelvic malignant tumors: A study of nine patients. Issue 1 (28th January 2019) - Uehara, Keiichiro; Kawakami, Fumi; Hirose, Takanori; Morita, Hiroki; Kudo, Eiji; Yasuda, Masanori; Märkl, Bruno; Zen, Yoh; Itoh, Tomoo; Imai, Yukihiro
Abstract : The clinicopathological and immunohistochemical characteristics of clinically occult extrapulmonary lymphangioleiomyomatosis in lymph nodes (LN‐LAM) being dissected during surgical staging of pelvic malignancy have not been well investigated. We assessed samples from nine female patients (median age, 61). None had past or familial history of tuberous sclerosis and had LAM lesions other than LN such as lung. The primary malignancies included four endometrial endometrioid carcinomas, one endometrial carcinosarcoma, three ovarian serous carcinomas and one urothelial carcinoma. Median follow‐up was 43 months. The number of affected LNs ranged from 1 to 15 (median, 2) with sizes ranging from 1 to 13 mm (median, 3.0). Six cases had clinically occult LN‐LAM only within the pelvic LNs, two only within para‐aortic LNs, and one within both pelvic and para‐aortic lymph nodes. Immunohistochemically, LAM cells exhibited a strong diffuse positivity for β‐catenin and E‐cadherin in all nine cases. Clinically occult LN‐LAM mainly affects peri‐ or post‐menopausal women. On rare occasions, occult LN‐LAM may manifest as systemic LAM, including in the lung. β‐catenin and E‐cadherin carry potential utility as additional diagnostic markers.